Stress, lipid profile and inflammatory responses to flunixin meglumine administration in surgical and non-surgical castration in donkeys - Hamidreza Alipour-Khairkhah; Saeed Azizi; Siamak Asri-Rezaei (Veterinary and Animal Science, 2025)
Donkeys are in the Equidae family but have several differences from horses. There are many studies on the pathophysiology of pain and its clinical signs in horses, but data are limited for donkeys. Therefore, the present study aimed to investigate biochemical effects of flunixin meglumine in donkeys subjected to pain induced by bloodless and surgical castration. Twenty healthy male donkeys were randomly divided into four groups: 1- Surgical castration with flunixin injection, 2- Surgical castration without flunixin injection, 3- Non-surgical castration with flunixin injection, and 4- Non-surgical castration without flunixin injection. Blood samples were collected a day before surgical procedures; four hours, one day, and two days after castration. Serum levels of IL-6, TNF-α, CRP, fibrinogen, cortisol, triglyceride, and cholesterol significantly increased in non-surgical castrated group compared to the other groups. Moreover, the levels of the measured parameters were significantly higher in the non-surgically castrated group compared to the surgically castrated group. Furtheremore, flunixin meglumine administration reduced the levels of the mentioned parameters, and it was significant for TNF-α and fibrinogen in the surgically castrated donkeys. However, in the nonsurgically castrated animals, there was a significant reduction in the levels of all mentioned parameters except for fibrinogen. It was concluded that non-surgical method, compared to the surgical method, was accompanied by more inflammation, stress, and pain; therefore, the surgical method could be suggested as a preferred technique for the castration of donkeys. Furthermore, the injection of flunixin meglumine could be suggested in the castration of donkeys, particularly in the bloodless technique.